IMPLIKASI HUKUM HAK TANGGUNGAN BAGI KREDITOR SEPARATIS DALAM PROSES KEPAILITAN DEBITOR: STUDI PUTUSAN NO. 20/PDT.SUS-GUGATAN LAIN-LAIN/2023/PN.NIAGA.SMG - Yunianti, Devi; Abdullah, Ali; Triwulandari, Endah (Jurnal Ilmiah Advokasi, 2025)
The position of secured creditors in Indonesian bankruptcy law raises critical issues regarding the limits of execution rights and the protection of stakeholders’ interests. This study specifically examines these dynamics through the case study of Decision Number 20/Pdt.Sus-Gugatan Lain-Lain/2023/PN.Niaga.Smg. Using a normative juridical approach, the research analyzes the execution rights of secured creditors, particularly holders of security rights, within the framework of prevailing bankruptcy law. The findings reveal that although secured creditors enjoy privileged rights, their enforcement is subject to strict legal procedures, including a 90-day execution moratorium following the bankruptcy ruling. These results highlight a shift in Indonesian bankruptcy law toward a more responsive and adaptive system, functioning not only as a debt resolution mechanism but also as an instrument to maintain economic balance and social justice Keywords: Bankruptcy; Separatist Creditors; Mortgage Rights